2020
DOI: 10.1088/2051-672x/ab8aa5
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization, mechanical and abrasion resistance of nanocellulose-reinforced wood panels

Abstract: Cellulose nanocrystals (CNCs) are promising particles in the production of wood fibre nanocomposites, due to their high stiffness, mechanical strength and low density. Wood fibres are the main source of cellulose, thus allowing the direct extraction of CNCs. As an attempt to improve the quality of wood fibre panels, this work performed topographical, tribological and mechanical characterization of medium density fibreboard (MDF) reinforced with CNCs at different concentrations, by substituting from 2 to 6% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Activities related to tribology and surface engineering at the Federal University of Rio Grande -FURG started in 2016 when Prof. Henara Costa moved from LTM/ UFU to FURG, culminating with the creation of the Laboratory of Surface Engineering (LabSurf) in 2019. The works span from surface engineering techniques such as surface modifications [113,280,[320][321][322][323][324][325][326][327][328][329][330][331][332] and different coating technologies [112,113,[333][334][335] to their effects on surface topography [102,103,121,326,[336][337][338], surface hardness [339][340][341], machinability [2], formability [337,342,343], corrosion [335,[344][345][346], tribological performance [13, 50-52, 113,280,320,322,333,337,347,348] and tribo...…”
Section: Brazilian Tribology: Status Quomentioning
confidence: 99%
See 1 more Smart Citation
“…Activities related to tribology and surface engineering at the Federal University of Rio Grande -FURG started in 2016 when Prof. Henara Costa moved from LTM/ UFU to FURG, culminating with the creation of the Laboratory of Surface Engineering (LabSurf) in 2019. The works span from surface engineering techniques such as surface modifications [113,280,[320][321][322][323][324][325][326][327][328][329][330][331][332] and different coating technologies [112,113,[333][334][335] to their effects on surface topography [102,103,121,326,[336][337][338], surface hardness [339][340][341], machinability [2], formability [337,342,343], corrosion [335,[344][345][346], tribological performance [13, 50-52, 113,280,320,322,333,337,347,348] and tribo...…”
Section: Brazilian Tribology: Status Quomentioning
confidence: 99%
“…In terms of nanotechnology, the effects of the reinforcement of wood panels with nanocellulose particles on surface topography, hardness and abrasion resistance have been investigated [336,350,351]. Niobium pentoxide nanoparticles have resulted in more refined and adherent coatings when added during the electrodeposition of Zn-Ni coatings [13].…”
Section: Brazilian Tribology: Status Quomentioning
confidence: 99%
“…In this review paper, the description of different types of nanocellulose is first reported, and then several characterization methods used to analyze them. Finally, the most recent applications of these innovative nanomaterials in the artistic context have been collected; nanocellulose has proved to be useful for several purposes, such as: ancient and degraded wood consolidation, wood reinforcement coating, the consolidation of waterlogged wooden artifacts, and structural reinforcement for canvases degraded by aging [18,19,[21][22][23][24][25]. The novelty of this review, which aims to offer an interesting overview about the use of nanocellulose for the recovery and conservation of cultural heritage, lies in having collected the latest applications of this bio-nanomaterial for the treatment of several artworks in a single paper.…”
Section: Introductionmentioning
confidence: 99%